Sofia's puppy love - Velasquez, Crystal (New York, NY : Scholastic Inc., 2018)
When a litter of puppies is born at the animal shelter, Sofia's mom says they may adopt one if Sofia proves she can take care of it, but she soon learns that puppy care is more difficult than she imagined.
At head of title: American Girl.
Keywords: Dogs -- Fiction; Pet adoption -- Fiction